Chest radiograph image enhancement with wavelet decomposition and morphological operations - Anthony Y. Aidoo; Matilda Wilson; Gloria A. Botchway (Universitas Ahmad Dahlan, 2019)
Medical image processing algorithms significantly affect the precision ofdisease diagnostic process. This makes it crucial to improve the quality of a medical image with the goal to enhance perceivability of the points of interest in order to obtain accurate diagnosis of a patient. Despite the reliance of various medical diagnostics on utilize X-rays, they are usually plagued by dark and low contrast properties. Sought-after details in X-rays can only be accessed by means of digital image processing techniques, despite the fact that these techniques are far from being perfect. In this paper, we implement a wavelet decomposition and reconstruction technique to enhance radiograph properties, some of which include contrast and noise, by using a series of morphological erosion and dilation to improve the visual quality of the chest radiographs for the detection of cancer nodules.